Reflections beyond implementation: Evaluation of the project-based learning in the research curriculum of the Philippine Science High School - Luzon campuses - Dacumos, Leo Peter; Silva, Dorothy (Universitas Terbuka, 2023)
STEM schools have put priority on establishing research education as a core program that enables students to choose a topic of their choice, identify a problem, and find a solution to it through experimentation and other modes of data collection. At the Philippine Science High Schools, one of its key goals is to foster a research culture among its scholars, who will help to strengthen the country's academic and scientific workforce and contribute to its success in the future. To improve instructional teaching, the project-based learning (PBL) approach has been utilized in many academic courses. A cache of studies has delved into the use of project-based learning approaches in many academic courses but the research education. This research project aimed to evaluate the implementation of project-based learning (PBL) in the STEM Research curriculum of the Philippine Science High School – Luzon campuses. Select teachers from the Philippine Science High School have shared their thoughts through the qualitative interview tool. The use of qualitative interview tool is aimed to explore their thoughts and opinions regarding the various aspects of project-based learning (PBL) implementation within the PSHS research curriculum. Thematic analysis using phenomenological reduction shows emerging themes highlighting the benefits, challenges, and things that are needed to start to improve the implementation of the project-based learning approach within the research curriculum of the PSHS system.